The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13061780
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome as a Therapy in Pouchitis and Ulcerative Colitis

Abstract: The gut microbiome has been implicated in a range of diseases and there is a rapidly growing understanding of this ecosystem’s importance in inflammatory bowel disease. We are yet to identify a single microbe that causes either ulcerative colitis (UC) or pouchitis, however, reduced microbiome diversity is increasingly recognised in active UC. Manipulating the gut microbiome through dietary interventions, prebiotic and probiotic compounds and faecal microbiota transplantation may expand the therapeutic landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 89 publications
0
13
0
1
Order By: Relevance
“…Recently, many studies have shown that intestinal microbial balance is related to UC [2,12,13]. Compared with healthy people, the diversity and abundance of gut microbes in UC patients decreased, which was related to the increased risk of disease recurrence [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have shown that intestinal microbial balance is related to UC [2,12,13]. Compared with healthy people, the diversity and abundance of gut microbes in UC patients decreased, which was related to the increased risk of disease recurrence [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ripened Pu-erh tea can promote the production of SCFAs, important gut microbial metabolites, to improve DSS-induced colitis [21]. The existing evidence suggests that a diet rich in bioactive substances can be a promising intervention strategy for the management of UC [13,17,18]. On the other hand, immune dysfunction caused by intestinal mucosal damage was considered one of the leading causes of UC [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that a combination of the two antibiotics can be effective also in patients with refractory/recurrent pouchitis [67]. The mechanisms implicated in the pouch microbiota's changes after antibiotic therapy that are responsible for their favorable effects are not clearly understood [38]. In the study of Gosselink et al, ciprofloxacin could eradicate pathogens that are significantly increased during pouchitis (Clostridium perfringens, hemolytic Escherichia coli) while not disrupting most of the anaerobic bacteria that contribute to the stability of the IPAA's flora [36].…”
Section: Antibioticsmentioning
confidence: 99%
“…Interestingly, the majority of the relapses occurred during or shortly after the completion of FMT [80,81]. Overall, only a few studies have explored the role of FMT in chronic pouchitis so far, exhibiting some pitfalls such as the heterogeneity in study design and type of fecal transplant delivery [38]. Future specifically dedicated RCTs with large sample-sizes and standardized protocols (i.e., disease definitions, type of FMT delivery, dose, or duration) will help to ensure reproducible data and provide higher quality of evidence on the real efficacy of FMT in the treatment of chronic pouchitis [82].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
See 1 more Smart Citation